The contribution of gastric emptying scintigraphy to the treatment of obesity with gastric bandage--preliminary results - Hladik, Pavel; Vizda, Jaroslav; Mala, Eva; Zadak, Zdenek; Hroch, Tomas (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2008)
INTRODUCTION: Gastric banding for morbid obesity is among the least mutilating of procedures used in bariatric surgery and is classified as a restrictive surgical method. Although it is widespread, so far, however the mechanism responsible has not been fully explained. METHODS AND RESULTS: The authors present the preliminary results from scintigraphic examination of the evacuation ability of the stomach using food labeled with (99m)Tc-colloid in six obese patients with a gastric bandage. This initial study showed that the functionality of the bandage demonstrated as a significant drop in body weight, is connected with slower evacuation of the stomach. However, the use of adjustable bandages would have significantly slowed and restricted the passage of food through the cardia of the stomach. CONCLUSIONS: Since it can be extremely difficult to adequately objectively determine the functionality of gastric bandages, evaluating the gastric emptying scintigraphy may be useful in fulfilling this purpose.
Keywords: Stomach; Middle Aged; žaludek; Gastroplasty; radioisotopová scintigrafie; Radionuclide Imaging; gastroplastika; dospělí; Humans; Adult; Weight Loss; Gastric Emptying; hmotnostní úbytek; Obesity, Morbid; vyprazdňování žaludku; morbidní obezita; lidé; lidé středního věku